Identifikasi Risiko Keselamatan Kerja Dengan Menggunakan Metoda Job Safety Analysis (JSA) Pada Rencana Proyek Perkantoran Terpadu Kota Payakumbuh - Desman, Sutria; Ridha Sari; Hanifah Hasnur (Universitas Andalas, 2023)
Office facilities and infrastructure are one of the main components supporting the running of government activities in an area, which aims to provide services to the community. Therefore, the Payakumbuh City Government will carry out work to build an office complex consisting of the Health Service Office, Inspectorate Office, Social Service Office and Environmental Service Office. Based on PUPR Ministerial Regulation No. 10 of 2021, it is required that before construction work is carried out, an Occupational Health and Safety study or known as Job Safety Analysis (JSA) must first be carried out. This research was conducted using a semi-qualitative method with analysis of the judgments of experts (justice professionals) which aims to transform raw data into easy-to-understand information in the form of more concise and clear information. In this research, an analysis was carried out to determine the possible risk of occupational hazards based on the frequency and severity values resulting from work, guided by PUPR Ministerial Decree No. 10 of 2021. Based on the research results, it was found that the level of potential risk of occupational accident hazards was divided into 3: major risk level, medium risk level and high level. small risk. There are 4 variables at the high risk level, 20 variables at the medium risk level and 26 variables at the small risk level. Of the three risk level categories, mitigation can be done using control methods such as substitution, elimination, engineering and administrative control methods.